2019
DOI: 10.1002/dc.24343
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic features of vaping‐induced lung injury: A case report

Abstract: Vaping‐induced lung injury is a recently recognized phenomenon owing to the rising popularity of e‐cigarette use. A cluster of cases of varying severity, including six deaths, was recently reported in the United States by the Centers for Disease Control. The objective of this report is to highlight the cytologic features suggestive of vaping‐induced lung injury. A 20‐year‐old previously healthy man presented with a 7‐day history of progressively worsening respiratory symptoms including dyspnea on exertion, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Tables 2 and 3. Most common diagnosis was EVALI (n = 15) [26][27][28][29][30][31][32][33][34][35][36] or EVALI with an additional finding (n = 1) [37]. Second most common diagnosis included either organizing pneumonia/ Bronchiolitis obliterans with organizing pneumonia (BOOP)/ respiratory bronchiolitis (n = 12) [38][39][40][41][42][43][44][45][46] or lipoid pneumonia (n = 9) [11,[47][48][49][50][51].…”
Section: Classification Of Casesmentioning
confidence: 99%
“…Tables 2 and 3. Most common diagnosis was EVALI (n = 15) [26][27][28][29][30][31][32][33][34][35][36] or EVALI with an additional finding (n = 1) [37]. Second most common diagnosis included either organizing pneumonia/ Bronchiolitis obliterans with organizing pneumonia (BOOP)/ respiratory bronchiolitis (n = 12) [38][39][40][41][42][43][44][45][46] or lipoid pneumonia (n = 9) [11,[47][48][49][50][51].…”
Section: Classification Of Casesmentioning
confidence: 99%
“…In our case, the Oil Red O stain, which stains the lipid droplets in macrophages/ histiocytes, was strongly positive in the sections from the patient's lungs. This is supporting evidence of vaping, but it is not specific [9][10][11]. However, acute inhalational injury was documented by video bronchoscopy, and this provided confirmatory evidence of the vaping-induced lung injury [3-7, 12, 13].…”
Section: Discussionmentioning
confidence: 80%
“…In cases that did have ORO stain performed on BAL specimens, variable findings have been reported. Several single case reports have described cases of EVALI with abundant OPM in BAL 4,8,10,11 . A report by Ocampo‐Gonzalez et al specified a threshold OPM count of 80% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This makes BAL an invaluable specimen in prospective EVALI patients, in many of whom lipid‐accumulating lung injuries have been shown to occur. Several investigations have shown that many EVALI patients had ORO‐positive, lipid‐laden alveolar macrophages (OPM) in their BAL specimens 4‐12 . Based on these observations, ORO in BAL specimens has been proposed as a potentially useful diagnostic tool in cases of suspected EVALI.…”
Section: Introductionmentioning
confidence: 99%